The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.injury.2017.10.040
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of postoperative weight bearing and management protocols for tibial plateau fractures: Findings from a scoping review

Abstract: Postoperative rehabilitation for TPFs most commonly involves significant non-weight bearing time before full weight bearing is recommended at 9-12 weeks. Partial weight bearing protocols and brace use were varied. Type of rehabilitation may be an important factor influencing recovery, with future high quality prospective studies required to determine the impact of different protocols on clinical and radiological outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 129 publications
1
36
0
2
Order By: Relevance
“…Tibial plateau fractures are articular injuries which have a broad spectrum of clinical presentations and are frequently associated with long term complications [1,2]. In recent years these challenging fractures have become a topic of great interest not only regarding their classification but also fixation methods and expected outcomes [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Tibial plateau fractures are articular injuries which have a broad spectrum of clinical presentations and are frequently associated with long term complications [1,2]. In recent years these challenging fractures have become a topic of great interest not only regarding their classification but also fixation methods and expected outcomes [3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 10 , 18 , 28 30 Most frequently, a variety of partial weight-bearing protocols for 4–6 weeks is preferred by the surgeons. 14 Interestingly, Thewlis et al 31 have shown with their gait analysis study that patients who are instructed to partial weight bear, they are self-regulating their weight-bearing status, but nevertheless this fact did not affect the outcomes. Kalmet et al in their retrospective study comparing partial weight bearing with restrictive weight bearing after plate fixation of tibial plateau fractures report no differences in terms of complications and patient reported outcome measure (PROM) outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The use of the brace could vary from 10 days to 6 weeks. 19 , 20 The use of braces as a post-operative type of immobilisation is not frequently reported in the literature, with only one-third of the studies found by Arnold et al 14 recommending its use.…”
Section: Discussionmentioning
confidence: 99%
“…Bracing postoperatively is common practice with rigid braces holding the knee in extension, or more commonly hinged braces used for 3-6 weeks [120]. However, a recent prospective trial conducted by Chauhan et al [121] found no significant difference between 6 weeks of bracing and no bracing at all after ORIF of tibial plateau fractures for union rates, postoperative range of motion, and Medical Outcomes Study 36-Item Short Form scores.…”
Section: Bracingmentioning
confidence: 99%
“…Full weight-bearing is commonly delayed for 9-12 weeks with 4-6 weeks of nonweight bearing followed by 4-6 weeks of partial weight-bearing [120]. Two recent retrospective articles with sample sizes of 17 and 90 have challenged this notion with excellent results with immediate full weight bearing as tolerated [122,123].…”
Section: Weight Bearingmentioning
confidence: 99%